Integração de veículos elétricos em redes inteligentes para otimização e suporte à geração distribuída - Salvatti, Gabriel Antonio (2020)
The concept of microgrids configured as smart grids has been increasingly widespread worldwide and is inevitable for the future of the electrical system. The growth of a decentralized generation (DG), which is located with the consumers themselves, has intensified recently due mainly to technological availability, reduction of implementation costs and flexibility of the legislation. Therefore, the complexity of the electrical system has grown in the presence of these new generating units, raising several questions about problems in the energy supply, quality, among others. Thereby, methods must be developed to optimize and monitor the management of these new units in order to improve the efficiency and stability of the electrical system. In this context, a new approach is proposed with the use of electric vehicles (EV) aiming to optimize the participation of DG in the system to support the generation irregularities and high demands profiles. EVs are increasingly present in the current scenario and appear as a good alternative to other types of energy storage systems (ESS), e.g., such as stationary batteries. Therefore, this work approaches an energy management strategy for microgrids allowing the interaction of EV with photovoltaic generation (PV) and consumer loads using a configuration that uses a shared AC bus. This management approaches economic and quality aspects in the use of energy, making different operation modes available to users. The simulations are performed using a script developed in the software Matlab taking different characteristics into account adopted by users, and it was confirmed the suitable behavior of the manager’s operation. The emulation results are performed with dSPACE MicroLabBox and Raspberry Pi 3 and support the responses achieved in the simulations. The results obtained indicate the necessity of an energy management system (EMS) for microgrids with multiple elements that allows the coordination of all of them while increases the efficiency and reliability of the system.